Citizen-Editors' Endogenous Information Acquisition and News Accuracy - Francesco Sobbrio (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2013)
This paper provides a model of the market for news where profit-maximizing media outlets choose their editors from a population of rational citizens. The analysis identifies a novel mechanism of media bias: the bias in a media outlet's news reports is the result of the slanted endogenous information acquisition strategy of its editor. In particular, the results show that the expected accuracy of news reports is lower the more ideological an editor is. Nevertheless, citizens find it optimal to acquire information from a media outlet whose editor has similar ideological preferences. Depending on the distribution of citizens' ideological preferences, a media outlet may choose an ideological editor even in a monopolistic market. Moreover, ideological editors are more likely to be present in the market for news: i) the higher the number of media outlets competing in the market for news; ii) the lower the opportunity cost that citizens have to incur to acquire information
Keywords: D81; D82; L82; 330; Media Bias; Slant; Information Acquisition; Valence; Competition